Nas trilhas do dito e do escrito: práticas de ensino de leitura na educação infantil em Catalão – GO - (:unkn) unknown (Universidade Federal de Goiás, 2018)
Reading has a social function enabling the individual to insert and participate in the most diverse activities required in a literate universe. This diversity presupposes that the individual, as a reader, can through a process of interaction, demonstrate expressions of understanding, interpretation and understanding of what he reads. In view of this context, in this research I proposed to answer the following question: "How are the teaching practices of pre-school teachers for the formation and development of the reader developed?”Therefore, in the general objective I sought to know the teaching practices used in the work of teachers of early childhood education for the formation and development of the reader. Specifically, I tried to identify which strategies were used in teaching practices for the formation and development of the reader. Also, understand the conceptions of reading of the teachers of early childhood education. And lastly, I tried to understand also the proposal of reading brought in the political-pedagogical project of the researched institutions. In view of this, I discussed the importance of reading for the insertion of individuals in society, understanding it within a historical, social and cultural process, considering that already in children's education, children need to have access to reading teaching from practices that contemplate understanding. For the development of this study, I used a methodology based on qualitative research, with support in some elements of the ethnographic method, such as participant observation, semi-structured interview and documentary analysis. Thus, I conducted the research in the city of Catalão - GO, having as subjects three teachers, who work in three municipal schools in this city. I supported authors who discuss the subject matter as Girotto e Souza (2010; 2011); Solé (1998); Bortoni-Ricardo (2010; 2012); Kleiman (2002, 2005); Freire (1994); Koch and Elias (2012); Marcuschi (2008); Bajard (2005; 2007); Antunes (2003); Soares (2000), among other authors that deal with the subject. Based on the studies carried out, the data revealed that the teaching practices of reading developed by Jardim II teachers, mostly, have been based on the reading of statements of the questions proposed in the apostille material. I found in these practices, indications of strategies of reading comprehension, however, these were used in an intuitive way, since, the teachers do not have theoretical knowledge about this subject. The political-pedagogical projects in force during the period under investigation, emphasized the importance of reading, however, what was written in the documents, not always, dialogued with the teaching practices. The results also showed that the teachers' conceptions about reading are characterized by a hybridity, being that they were used in reading as decoding, mainly with mechanical activities, and in some moments, in the search for reading comprehension. Finally, I emphasize that knowledge about reading strategies is necessary so that reading can be carried out from situations that give the students an opportunity to understand, and that are developed from early childhood education, contributing to the formation of the critical reader, reflective, that is able to position itself before different situations that are demands in the society.
In the tracks of dito and writing: practices reading teaching in early childhood Education in Catalão – GO
Keywords: Ensino de leitura; Estratégias de leitura; Práticas docentes; Reading teaching; Reading strategies; Teaching practices; EDUCACAO::ENSINO-APRENDIZAGEM